IL-1beta processing in host defense: beyond the inflammasomes. - Mihai G Netea; Anna Simon; Frank van de Veerdonk; Bart-Jan Kullberg; Jos W M Van der Meer; Leo A B Joosten (PLoS Pathogens, 2010)
Stimulation and release of proinflammatory cytokines is an essential step for the activation of an effective innate host defense, and subsequently for the modulation of adaptive immune responses. Interleukin-1beta (IL-1beta) and IL-18 are important proinflammatory cytokines that on the one hand activate monocytes, macropages, and neutrophils, and on the other hand induce Th1 and Th17 adaptive cellular responses. They are secreted as inactive precursors, and the processing of pro-IL-1beta and pro-IL-18 depends on cleavage by proteases. One of the most important of these enzymes is caspase-1, which in turn is activated by several protein platforms called the inflammasomes. Inflammasome activation differs in various cell types, and knock-out mice defective in either caspase-1 or inflammasome components have an increased susceptibility to several types of infections. However, in other infections and in models of sterile inflammation, caspase-1 seems to be less important, and alternative mechanisms such as neutrophil-derived serine proteases or proteases released from microbial pathogens can process and activate IL-1beta. In conclusion, IL-1beta/IL-18 processing during infection is a complex process in which the inflammasomes are only one of several activation mechanisms.